2020
DOI: 10.3390/ani10101921
|View full text |Cite
|
Sign up to set email alerts
|

High Exposure to Toxoplasma gondii and Neospora Spp. in Donkeys in Israel: Serological Survey and Case Reports

Abstract: Toxoplasma gondii and Neospora spp. are closely related cyst-forming coccidian parasites, which infect various animal species and have considerable zoonotic and economic implications, respectively. Both parasites are endemic in Israel and have been reported to infect wild and domestic animals. This study was conceived to evaluate the serologic exposure of donkeys to these parasites. Serum samples were collected from 98 donkeys. Half of them (n = 49) were from animal shelters in Israel, and the rest (n = 49) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Low antibody titers were also observed by James et al [23], in which 73% (239/328) of the animals titrated below 1:100 for anti-T. gondii, and by Bartová et al [24], who observed that all positive animals for anti-T. gondii (3%; 19/643) and for anti-N. caninum (2.3%; 15/6430) antibodies titrated up to 1:100. Low titers for anti-T. gondii in horses should not be ignored [25], as they commonly develop lower antibody titers [26,27]. In infections by other pathogens, they found that high titers of antibodies were observed after recent contact with the antigen, indicating acute infection, in addition to low titers in chronic infections, denoting old contact with the agent [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Low antibody titers were also observed by James et al [23], in which 73% (239/328) of the animals titrated below 1:100 for anti-T. gondii, and by Bartová et al [24], who observed that all positive animals for anti-T. gondii (3%; 19/643) and for anti-N. caninum (2.3%; 15/6430) antibodies titrated up to 1:100. Low titers for anti-T. gondii in horses should not be ignored [25], as they commonly develop lower antibody titers [26,27]. In infections by other pathogens, they found that high titers of antibodies were observed after recent contact with the antigen, indicating acute infection, in addition to low titers in chronic infections, denoting old contact with the agent [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…to be 40% in horses and 52% in donkeys. According to Tirosh-Levy et al (48), it was as high as 70% in donkeys. Sevgili et al (44) reported the seroprevalence of Neospora sp.…”
Section: Componentmentioning
confidence: 96%
“…Balkaya et al (7) found that the prevalence of the parasite was 62%, which is also compatible with our result. However, T. gondii is common not only in equids, but also in other mammalian species, such as sheep, cattle, cats, dogs, and humans, in Turkey and worldwide (20,25,48). It can be suggested that T. gondii is highly prevalent in Turkey in both humans and other mammalians, which is a very prominent problem for public health (7,15).…”
Section: Componentmentioning
confidence: 99%
“…Toxoplasma gondii is a very important food-borne zoonotic pathogen that can infect almost all warm-blooded animals, including humans, livestock and birds [8][9][10][11][12][13][14] and also causes economic losses in the livestock industry [15][16][17]. Tibetan sheep and yaks are indigenous species raised under extensive animal systems, while cows, chickens, pigs, and horses are important economic livestock animals in the QTPA.…”
Section: Introductionmentioning
confidence: 99%